Cost-effectiveness of using an extensively hydrolyzed casein formula plus the probiotic Lactobacillus rhamnosus GG compared to an extensively hydrolyzed formula alone or an amino acid formula as first-line dietary management for cow’s milk allergy in the US - Ovcinnikova O; Panca M; Guest JF (Dove Medical Press, 2015)
Olga Ovcinnikova,1 Monica Panca,1 Julian F Guest1,2 1CATALYST Health Economics Consultants, Northwood, London, 2Faculty of Life Sciences and Medicine, King’s College, London, UK Objectives: The aim was to estimate the cost-effectiveness of using an extensively hydrolyzed casein formula (eHCF) plus the probiotic Lactobacillus rhamnosus GG (eHCF + LGG; Nutramigen LGG) compared to an eHCF alone (Nutramigen) and an amino acid formula (AAF; Neocate) as first-line dietary management for cow’s milk allergy (CMA) in the US. Methods: Using a cohort study design, the analysis was based on the case records of 136 eHCF-fed, 59 eHCF + LGG-fed, and 217 matched AAF-fed infants extracted from the Truven Health MarketScan® Commercial Claims Database (a nationally representative database of the commercially insured population of the US). Clinical outcomes and health care resource use (with corresponding costs at 2012 prices), following first-line dietary management with each formula, were estimated over 12 months from the start of feeding. Differences in infants’ outcomes and resource use between groups were adjusted for any differences in baseline covariates. Results: Infants were <6 months of age at presentation. Fifty-six percent of eHCF + LGG-fed infants were estimated to have been successfully managed by 9 months compared to 38% of eHCF-fed infants and 35% of AAF-fed infants (P<0.05 and P=0.003 respectively). Infants in the AAF group used significantly more health care resources and prescribed drugs than infants in the other two groups. The estimated cost of managing a CMA infant over the first 12 months following the start of feeding was $3,577, $3,781, and $6,255 for an eHCF + LGG-fed, eHCF-fed, and AAF-fed infant, respectively. Parents’ costs accounted for up to 10% of the total costs and the remainder was incurred by insurers. The analyses were robust to plausible changes in all variables. Conclusion: Using real world evidence, initial dietary management with eHCF + LGG appears to afford a more cost-effective use of health care resources than initial dietary management with eHCF or AAF since it releases health care resources for alternative use within the system and reduces costs without impacting on the time needed to manage the allergy. Keywords: amino acid formula, cost-effectiveness, cow’s milk allergy, economic evaluation, extensively hydrolyzed formula, Lactobacillus rhamnosus GG, Neocate, Nutramigen, US